2017
DOI: 10.1016/j.actamat.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation loop evolution during in-situ ion irradiation of model FeCrAl alloys

Abstract: Model FeCrAl alloys of Fe-10%Cr-5%Al, Fe-12%Cr-4.5%Al, Fe-15%Cr-4%Al, and Fe-18%Cr-3%Al (in wt %) were irradiated with 1 MeV Kr ++ ions in-situ with transmission electron microscopy to a dose of 2.5 displacements per atom (dpa) at 320C. In all cases, the microstructural damage consisted of dislocation loops with ½〈111〉 and 〈100〉 Burgers vectors. The proportion of ½〈111〉 dislocation loops varied from ~50% in the Fe-10%Cr-5%Al model alloy and the Fe-18Cr%-3%Al model alloy to a peak of ~80% in the model Fe-15%Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(21 citation statements)
references
References 33 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…The 〈100〉 type loops are more stable at higher temperatures [34], with the loop Burgers vectors transitioning from majority 〈111〉 to majority 〈100〉 between 300°C and 400°C [35]. The observation of a greater number of 〈100〉 loops for a constant temperature usually suggests that 〈111〉 defects (produced in-cascades) were more mobile [74,75], as it implies 〈100〉 loop production via the 111-mechanism [72] occurs more frequently. This suggests that the loops produced during self-ion irradiation may have been more mobile than loops produced during neutron irradiation, despite the neutron irradiation being the hotter experiment.…”
Section: -On the Formation Of Dislocation Loopsmentioning
confidence: 99%
“…The 〈100〉 type loops are more stable at higher temperatures [34], with the loop Burgers vectors transitioning from majority 〈111〉 to majority 〈100〉 between 300°C and 400°C [35]. The observation of a greater number of 〈100〉 loops for a constant temperature usually suggests that 〈111〉 defects (produced in-cascades) were more mobile [74,75], as it implies 〈100〉 loop production via the 111-mechanism [72] occurs more frequently. This suggests that the loops produced during self-ion irradiation may have been more mobile than loops produced during neutron irradiation, despite the neutron irradiation being the hotter experiment.…”
Section: -On the Formation Of Dislocation Loopsmentioning
confidence: 99%
“…Neutron and ion irradiation in the temperature range of 334°C to 384°C up to 2.5 dpa have been shown to produce a mixed population of dislocation loops with either a Burgers vector of 2 ⁄ 〈111〉 which can be either interstitial or vacancy in nature or 〈100〉 with interstitial nature [19,96,97]. Determination of the Burgers vectors of the dislocation loops is of high importance for irradiated FeCrAl alloys.…”
Section: Dislocation Loop Morphologiesmentioning
confidence: 99%
“…Composition also plays a role on the evolution of dislocation loops under irradiation. In-situ ion irradiations at 320°C have shown that dislocation loop densities are higher in low-Cr (10-12 wt.%) FeCrAl alloys compared to higher Cr variants [97]. Additionally, the ratio of 2 ⁄ 〈111〉 to 〈100〉 dislocation loops also increased with increasing Cr content.…”
Section: Dislocation Loop Morphologiesmentioning
confidence: 99%
“…To enhance the safety and reliability of nuclear power, different strategies of accident-tolerant fuel (ATF) claddings are proposed [1,5,6]. Compared with the discovery of new materials such as SiC f /SiC [7,8], high entropy alloys [9], and FeCrAl alloys [10,11] to completely replace the Zr-based alloys, making a protective coating on the surface of Zr-based alloys not only significantly improves the high-temperature steam corrosion resistance [12][13][14], but also retains the advantages of the Zr component [15][16][17][18], and thus is considered as a more direct and feasible approach to ATF claddings [19].…”
Section: Introductionmentioning
confidence: 99%